Ответ:
..............................................
[tex] \frac{y + 4}{4} = \frac{3y - 4}{14} \\ 14(y + 4) = 4(3y - 4) \\ 14y + 56 = 12y - 16 \\ 14y - 12y = - 16 - 56 \\ 2y = - 72 | \div 2 \\ \\ y = - 36[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
..............................................
Ответ:
[tex] \frac{y + 4}{4} = \frac{3y - 4}{14} \\ 14(y + 4) = 4(3y - 4) \\ 14y + 56 = 12y - 16 \\ 14y - 12y = - 16 - 56 \\ 2y = - 72 | \div 2 \\ \\ y = - 36[/tex]